A study about consumers' acceptance towards Newton products / Ros Azman Shah Abdul Rahim ... [et al.] - Abdul Rahim, Ros Azman Shah; Abd Aziz, Rogayah; Talib, Faridah Hanim; Abdullah, Latifah; Abdullah, Norra; Omar, Natrah (1985)
This project paper reveals the perception of Newton products among consumers. Their acceptance and attitudes towards the products and the size of market segment, actually achieved in the effort of distributing them. The degree of acceptance indicates what is lacking in Newton products, that are present in order as part of the product attributes that would helps consumers to make their decisions in making a purchase. The findings would lead to steps to be taken in order to improve the marketability of Newton products.